2019
DOI: 10.1007/s10488-019-00999-y
|View full text |Cite
|
Sign up to set email alerts
|

Mutual Capacity Building to Reduce the Behavioral Health Treatment Gap Globally

Abstract: Use of lay health workers for the treatment of common mental disorders is an expanding, yet still underutilized, opportunity for closing the behavioral health treatment gap globally. In this commentary, we describe how "mutual capacity building," an equal exchange of ideas between low and middle-income countries (LMICs) and high-income countries (HICs) to promote shared learning, could promote the development and scale-up of therapies using lay health workers. We propose ways that task sharing models for behav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 22 publications
0
23
0
Order By: Relevance
“…The use of trained counsellors who were not their usual HIV care providers seemed to enhance the acceptability of screening and the brief alcohol reduction intervention. Professional counsellors are, however, absent from the current public health workforce, largely due to the country's chronic shortage of financial and human resources for mental health [32,33]. Implementing screening and brief alcohol reduction interventions on scale, therefore, will require alternative delivery agents.…”
Section: Discussionmentioning
confidence: 99%
“…The use of trained counsellors who were not their usual HIV care providers seemed to enhance the acceptability of screening and the brief alcohol reduction intervention. Professional counsellors are, however, absent from the current public health workforce, largely due to the country's chronic shortage of financial and human resources for mental health [32,33]. Implementing screening and brief alcohol reduction interventions on scale, therefore, will require alternative delivery agents.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, Datiko and Lindtjørn (66) found that involving Health Extension Workers (HEWs) in TB treatment was a cost-effective alternative to health facility delivery. Surprisingly, despite their potential to provide psychosocial support to the people at the community level in LMICs, particularly during this overwhelming situation, CHWs have been underutilized in this role (67,68).…”
Section: The Unrealised Potential Of Chws In Providing Psychosocial Supportmentioning
confidence: 99%
“…The silence surrounding mental health is empowered by stigma, fears, and labelling which cause individual and lonely suffering [27,28]. This is especially true in the context of the rapidly growing problem of mental health of whole societies [29][30][31]. Despite the large number of publications, as well as recently undertaken actions by the UN and its agency WHO (World Health Organisation), including for example very good publications such as the WHO Quality Rights [32] and MhGap toolkit [33,34] global mental healthcare is still underfinanced and in many countries neglected [35].…”
Section: Mental Health and Covid-19mentioning
confidence: 99%
“…This will increase the anthropo-pressure on the planet, which is in opposition to the Sustainable Development Goals (SDG) [5][6][7], especially "Promoting mental health and wellbeing" (SDG 3.4), "Making cities and human settlements safe, stable, sustainable and inclusive" (SDG 11) as well as other SDGs which are threatened by urban sprawl [7][8][9] (pp. [19][20][21][22][23][24][25][26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%